The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1021/bi700548a
|View full text |Cite
|
Sign up to set email alerts
|

Differential Stability of Dimeric and Monomeric Cytochrome c Oxidase Exposed to Elevated Hydrostatic Pressure

Abstract: Detergent-solubilized dimeric and monomeric cytochrome c oxidase (CcO) have significantly different quaternary stability when exposed to 2−3 kbar of hydrostatic pressure. Dimeric, dodecyl maltoside-solubilized cytochrome c oxidase is very resistant to elevated hydrostatic pressure with almost no perturbation of its quaternary structure or functional activity after release of pressure. In contrast to the stability of dimeric CcO, 3 kbar of hydrostatic pressure triggers multiple structural and functional alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
2
13
1
Order By: Relevance
“…These results newly indicate that band a 2 represents another rate-limiting step in human CcO assembly. Both Cox6a and Cox6b subunits, which are thought to be responsible for dimerization of CcO, are the first to dissociate from the bovine complex under various destabilizing conditions [30,31]. Thus, it appears plausible that the elevated levels of the assembly intermediate S3 in COX6A KD cells could stem from compromised binding of Cox6b, which might be contingent upon the concomitant assembly of Cox6a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results newly indicate that band a 2 represents another rate-limiting step in human CcO assembly. Both Cox6a and Cox6b subunits, which are thought to be responsible for dimerization of CcO, are the first to dissociate from the bovine complex under various destabilizing conditions [30,31]. Thus, it appears plausible that the elevated levels of the assembly intermediate S3 in COX6A KD cells could stem from compromised binding of Cox6b, which might be contingent upon the concomitant assembly of Cox6a.…”
Section: Discussionmentioning
confidence: 99%
“…The subcomplexes in COX6A1 KD cells are represented mainly by incomplete CcO assemblies that lack only few peripheral nuclear-encoded subunits. Exposure of isolated monomeric bovine CcO to hydrostatic pressure results in a mixture of 13-, 11-and 9-subunit CcO complexes [31]. Analysis of separated forms showed that both the 13-subunit complex as well as the 11-subunit form devoid of subunits Cox6a and Cox6b retained 85-90% of electron transport activity of the untreated enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Both forms efficiently transfer electrons and bind substrates (Suarez et al 1984), but heterodimerizing is necessary for proton pumping (Stanicová et al 2007). The monomer possesses 13 subunits.…”
Section: Cox Structurementioning
confidence: 99%
“…Detailed studies are lacking in cases where both isoforms are expressed in the same tissue as to whether there is positional segregation within the cell. It is also unknown whether any hybrid forms occur of the dimer, which under some conditions is the more stable form of COX (Stanicova et al, 2007). …”
Section: X3 Evolutionary Events Of Primate Cox and Cytochrome Cmentioning
confidence: 99%